Preparation of MgO added iron ore pellets and effects on a pilot scale blast furnace operation - Chun T.-J.; Mu G.-T.; Meng Q.-M.; Long H.-M.; Wang P.; Bic C.-G. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The preparation of MgO bearing iron ore pellets in the mini and pilot scales, and the application for 4070m3 blast furnace were conducted in this paper. The results show that with increasing the MgO content, the compressive strength of fired pellets decreased significantly, while the metallurgical performances, such as RI (reducibility index), RDI (reduction degradation index) and RSI (reduction swelling index) were improved. The scanning electron microscope with energy dispersive spectrometry was used to test the microstructures and the compositions of iron oxide, and the slag of pellets. With increasing the MgO content, MgO exists in the form of magnesium ferrite and monticellite, which presents the high melting temperature, decreasing the content of liquid phase. The pilot scale experiment was performed on a commercial running grate-rotary kiln with the annual output of 2.4 million tons of pellets, which agrees with the results obtained in the mini scale experiment. The application of MgO-bearing pellets was carried out in the 4070 m3 blast furnace of Meisteel China, and the production indexes improved with increasing the yield and reducing the coke ratio, and the total benefits are 7067 USD/d, which presents the superior economic benefits.